Students' perceptions of authenticity of plurilingual non-native teachers in multilingual higher education settings: an exploratory and comparative case study of Geneva and Hamburg. Issue 3 (3rd July 2019) - Yanaprasart, Patchareerat; Melo-Pfeifer, Sílvia
ABSTRACT: This paper addresses the issue of students' perceptions of non-native teacher authenticity, combining the literature accounts of authenticity in the fields of foreign language learning, and teacher authenticity (both teachers' skills and teachers' linguistic resources). The data Analysis from an exploratory and comparative angle, involving two European Higher Education Institutions, reveals that: (i) assessing plurilingual teachers whose mother tongue is not the language of instruction is contextually, institutionally and disciplinarily bound; (ii) students are aware of the constraints and opportunities related to the teaching situation and are willing to sacrifice some 'correctness' in order to gain in multilingual and intercultural 'depth'.